Evolutionary Origin and Conserved Structural Building Blocks of Riboswitches and Ribosomal RNAs: Riboswitches as Probable Target Sites for Aminoglycosides Interaction - Elnaz Mehdizadeh Aghdam; Abolfazl Barzegar; Mohammad Saeid Hejazi (Tabriz University of Medical Sciences, 2014)
Purpose: Riboswitches, as noncoding RNA sequences, control gene expression through direct ligand binding. Sporadic reports on the structural relation of riboswitches with ribosomal RNAs (rRNA), raises an interest in possible similarity between riboswitches and rRNAs evolutionary origins. Since aminoglycoside antibiotics affect microbial cells through binding to functional sites of the bacterial rRNA, finding any conformational and functional relation between riboswitches/rRNAs is utmost important in both of medicinal and basic research. Methods: Analysis of the riboswitches structures were carried out using bioinformatics and computational tools. The possible functional similarity of riboswitches with rRNAs was evaluated based on the affinity of paromomycin antibiotic (targeting "A site" of 16S rRNA) to riboswitches via docking method. Results: There was high structural similarity between riboswitches and rRNAs, but not any particular sequence based similarity between them was found. The building blocks including "hairpin loop containing UUU", "peptidyl transferase center conserved hairpin A loop"," helix 45" and "S2 (G8) hairpin" as high identical rRNA motifs were detected in all kinds of riboswitches. Surprisingly, binding energies of paromomycin with different riboswitches are considerably better than the binding energy of paromomycin with "16S rRNA A site". Therefore the high affinity of paromomycin to bind riboswitches in comparison with rRNA "A site" suggests a new insight about riboswitches as possible targets for aminoglycoside antibiotics. Conclusion: These findings are considered as a possible supporting evidence for evolutionary origin of riboswitches/rRNAs and also their role in the exertion of antibiotics effects to design new drugs based on the concomitant effects via rRNA/riboswitches.